2005
DOI: 10.1007/s00198-005-1895-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultraviolet radiation on the production of 25 hydroxyvitamin D in the elderly population in the city of São Paulo (23 o 34’S), Brazil

Abstract: The lack of vitamin D is a major changeable factor involved in the pathophysiology of osteoporosis. Since the major source for this hormone is its cutaneous synthesis via ultraviolet radiation (UVR), we studied the serum level of 25-hydroxyvitamin D (25OHD) in 250 free-living elderly people (79.1 years old) from a subtropical region according to the UVR incidence and its correlations with parathormone (PTH) and ionized calcium. UVR and 25OHD differed according to the season of the year (P<0.001), with greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 21 publications
3
66
2
6
Order By: Relevance
“…In Brazil, a study of 894 adults (mean age: 58.1 ± 12.0 years) in the State of Pernambuco found that the mean 25(OH) D concentration was 26.0 ± 10.3 ng/mL and that the prevalence of vitamin D deficiency was 28.5% (27). Another Brazilian study of elderly individuals (mean age: 79.1 years) in São Paulo during the winter found that the mean 25(OH)D concentration was 11.6 ng/mL (28). However, these discrepancies may be related to differences in the patients' mean age and the season of the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, a study of 894 adults (mean age: 58.1 ± 12.0 years) in the State of Pernambuco found that the mean 25(OH) D concentration was 26.0 ± 10.3 ng/mL and that the prevalence of vitamin D deficiency was 28.5% (27). Another Brazilian study of elderly individuals (mean age: 79.1 years) in São Paulo during the winter found that the mean 25(OH)D concentration was 11.6 ng/mL (28). However, these discrepancies may be related to differences in the patients' mean age and the season of the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Research reported at that meeting showed that adults must maintain a much higher blood vitamin D level than children, i.e., approximately 75 nM/L. Low levels of circulating vitamin D were reported for an elderly Brazilian population, which has a deficiency (25 nM/L; 15.4%) or insufficiency (25-50 nM/L; 41.9%) of vitamin D (1). To date, there are no reports regarding the serum level of vitamin D in the Brazilian population comparing age, gender, sun exposure, food intake, and related disease.…”
Section: Vitamin Dmentioning
confidence: 99%
“…However, such premise has been refuted by studies that prove the high frequency of vitamin D deficiency in the Brazilian population 13,[20][21][22] . A study that included 250 elderly people living in São Paulo demonstrated a high and unexpected prevalence of vitamin D deficiency (15.4%) and insufficiency (41.9%).…”
Section: Discussionmentioning
confidence: 99%
“…A study that included 250 elderly people living in São Paulo demonstrated a high and unexpected prevalence of vitamin D deficiency (15.4%) and insufficiency (41.9%). 21 Also in relation to Brazilian data, a study was performed with 16 healthy teenagers from the countryside of São Paulo and showed high prevalence (60%) of vitamin D insufficiency. 22 A study involving 603 normal volunteers, also from São Paulo, found mean value of 25(OH)D of 21.4 ng/mL, and 77.4% of the analyzed patients had vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%